(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
certain elements that compose matter emit particles and radiations spontaneousl Thisphenomenon ,s ref erred lo as • radioactivity’. It cannot b altered by application_ of heat. electncity or any other force and remams unchangeable Three different 1-.mds of rays, known as alpha, beta and gamma rays are associated with radioactivity Toe alpha rays consist of particles (nuclei of helium atoms) carrying a positive charge. The beta rays particles have negative charge (stream of electrones). The gamma rays are chargeless electromagnetic radiation with shorter wavelengths than any X-rays. Nuclear radiation arises from hundreds of different kinds of unstable atom While many exist in nature the majority are created m nuclear reaction. Nuclear fussion is the process of splitting atoms, or fissioning them. Nuclear fussion was discovered in 1938 after nearly five decades of work by Ernest Rutherford, Henri Becquerel, Marie Cruise and Pierre Cruise who elaborate that the nucleus though tightly bond, could undergo different forms or radioactive decay and could transmute into other elements. It is nuclear fission that produces energy for nuclear power Nuclear fission happens naturally every day. Uranium, for example, constantly undergoes spontaneou_s fission_ at a very slow rate. This is why the element em radiation, and why ifs natural choice for the induced fission that nuclear power plants require.